Jinghuaweikang capsule alleviates Helicobacter pylori-infected gastric mucosal inflammation and drug resistance by regulating intestinal microbiota and MAPK pathway - Yang, Yao; Jia, Xiao-Fen; Cui, Guang-Hui; Huang, Qiu-Yue; Lin, Miao-Miao; Shi, Zong-Ming; Ye, Hui; Zhang, Xue-Zhi (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHelicobacter pylori (H. pylori) infection represents a prevalent global health burden. Current eradication strategies are complicated by increasing antibiotic resistance and detrimental alterations to the gut microbiome. Jinghuaweikang capsule (JWC), a traditional Chinese medicine, has demonstrated efficacy against H. pylori, yet its mechanisms involving microbiota-inflammation interactions remain incompletely elucidated.AIMThis study aimed to investigate the effects of the JWC on gastric mucosal inflammation and the expression of drug-resistance genes in H. pylori-infected mice.MethodsSixty Kunming mice were randomly allocated into six groups, including normal control group (Control), model group (Model), Western medicine triple group (AC), low-dose JWC group (JWCL), medium-dose JWC group (JWCM), and high-dose JWC group (JWCH). A mouse model of H. pylori infection was established by intragastric administration of an H. pylori SS1 solution for two weeks. The efficacy of this model was evaluated using rapid urease test (RUT) and Warthin-Starry (WS) silver stain. Subsequently, the experimental cohort of mice underwent pharmacological intervention. Hematoxylin and eosin (HE) staining, enzyme-linked immunosorbent assay (ELISA), and quantitative real-time polymerase chain reaction (qRT-PCR) were used to assess the impact of JWC on inflammation within the gastric mucosa of mice infected with H. pylori. Metagenomic sequencing technology was used to identify alterations in the intestinal microbiota and antibiotic resistance genes in the murine models. Western blotting was used to assess the expression levels of proteins involved in the mitogen-activated protein kinase (MAPK) signaling pathway.ResultsJWC mitigated gastric mucosal inflammation induced by H. pylori infection and reduced the concentrations of interleukin- (IL-) 6, IL-1β, and tumor necrosis factor-α (TNF-α) while inhibiting gene expression level. Metagenomic sequencing revealed that triple therapy in Western medicine markedly diminished the diversity of the intestinal microbiota while elevating the abundance of antibiotic-resistance genes, including macB, arlR, evgS, tetA(58), and mtrA. The diversity and richness of the intestinal microbiota in the JWC group were comparable to those in the control group, with an increase in the abundance of beneficial bacteria such as Muribaculaceae_bacterium. Furthermore, the expression levels of the antibiotic resistance genes macB, tetA(58), bcrA, oleC, and arlS were downregulated. Moreover, the activation of MAPK signaling pathway components phospho-ERK and phospho-p38 was inhibited.ConclusionJWC preserves microbial diversity and promotes a beneficial compositional shift, mitigates the risk of antibiotic resistance, modulates the MAPK signaling pathway, and alleviates gastric mucosal inflammation in mice infected with H. pylori.